Conformers, Infrared Spectrum and UV-Induced Photochemistry of Matrix Isolated Furfuryl Alcohol - Araujo Andrade, C. (2012)
The infrared spectra of furfuryl alcohol (2-furanmethanol, FFA) were investigated for FFA monomers isolated in low-temperature argon matrices. The structural interpretation of the obtained experimental spectra was assisted by analysis of the molecule’s conformational landscape. According to the DFT(B3LYP)/6-311++G(d,p) calculations, five different minimum energy structures were found on the potential energy surface of the molecule. They can be defined by the orientation of the OCCO and CCOH dihedral angles: GG′, GG, TG, TT, GT (G = +gauche, G′ = −gauche, T = trans) and have a symmetry equivalent configuration: GG′ = G′G, GG = G′G′, TG = TG′, GT = G′T. When zero-point energies are taken into account, only three (GG′, GG, and TT) out of the five unique minima correspond to stable structures. The most stable conformer GG′ (OCCO, 72.7°; CCOH, −59.3°), which in gas phase at room temperature accounts for ∼65% of the total population, was the only form isolated in the argon matrices at 14 K. The other two relevant forms convert into conformer GG′ during matrix deposition. The low temperature glassy and crystalline states of FFA were also obtained and their infrared spectra assigned, suggesting the sole existence of the GG′ conformer also in these phases. The photochemical behavior of FFA induced in situ, by tunable UV-laser, was also studied. The longest wavelength resulting in photochemical changes in the structure of the irradiated sample was found to be λ = 229 nm. Such UV irradiation of the matrix-isolated FFA led to production of formaldehyde and different isomeric C4H4O species. Cycloprop-2-ene-1-carbaldehyde and buta-2,3-dienal (two conformers) are the main initial C4H4O photoproducts formed upon short-time excitation at λ = 229 nm. But-3-ynal (two conformers) was the principal photoproduct resulting from prolonged excitation at λ= 229 nm, being consumed upon irradiation at shorter wavelengths (λ < 227.5 nm). Vinyl ketene is produced from FFA in the trans conformation and undergoes isomerization to the cis form upon irradiation at λ < 227.5 nm. Cyclopropene, propyne, allene, and CO were also identified in the irradiated matrices (in particular at the later stages of irradiation), suggesting that the photoproduced aldehydes partially decarbonylate during the performed photochemical experiments.